ELEKTRON TA’LIM RESURSLARI INNOVATSION O‘QITISH USULI SIFATIDA - Nurmaxanov, K.E. (SCIENCE and SOCIETY, 2024)
In this article, improving the quality of training graduates of educational institutions is associated with the integrated use of electronic educational resources in combination with innovative forms and methods of teaching. The competent use of electronic educational resources, involving the appropriate adjustment of all components of the methodological learning system, contributes to the formation of an integrated educational trajectory, which greatly contributes to the achievement of modern educational goals.